The Influence Of Moral Reasoning On Internal Audit Quality With Auditor Competence As A Moderating Variable - Kusiyah, Kusiyah; Usmany, Paul; Susilawati, Made; As’ady, Mustofa; Sahri, Yulian (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Internal audit quality is the initial stage that greatly influences whether a company's audit quality is good or bad, as well as being the initial door to creating a company that is healthy, clean, accountable, transparent, and upholds every existing company and state regulations. There are a number of factors that can influence whether the quality of internal audit is good or bad, including the auditor's moral reasoning to find odd flaws, increase the detail of the audit, and so on. Therefore, this research aims to analyze the influence of Moral Reasoning on Internal Audit Quality with Auditor Competence as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research is primary data distributed to 300 BUMN internal auditors spread throughout Indonesia. This data uses a questionnaire method in its distribution containing the choices of agree, strongly agree, strongly disagree, disagree, and normal/average regarding auditor reasoning, auditor competence, and internal audit standards. Hasil penelitian menunjukkan jika the Moral Reasoning variable can have a positive relationship and a significant influence on Internal Audit Quality because the P-Values value is positive and is below the significance level of 0.05, namely 0.019. This is because good moral reasoning from an auditor can make the auditor prioritize the interests of the public/company/state rather than personal interests or only some parties. This proves that the author's first hypothesis and first belief can be accepted. Apart from that, the Auditor Competency variable can moderate the relationship between the Moral Reasoning variable and Internal Audit Quality because the P-Values value is in a positive direction and is far below the significance level of 0.05, namely 0.000, even smaller than the direct assessment of 0.019. This is because good Moral Reasoning makes auditors prioritize the public interest, if accompanied by good Auditor Competency, it will make the influence of Moral Reasoning on Internal Audit Quality more significant. In this way, the second hypothesis and the researcher's second belief can also be accepted.